Well-being and engagement: its implications for university policy on administrative employee’s wellness program - D. Aquino, John Michael; de Vera, Jayson L. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The well-being and engagement of administrative employees are critical to creating a productive and sustainable work environment. This study investigates causes of university administrative staff well-being and professional involvement. This study examines: i) employee engagement and well-being; ii) administrative employees’ biggest workplace challenges; and iii) how wellness programs promote personal and professional progress. This study used a concurrent triangulation mixed-method research approach. Gallup’s employee engagement survey found that 124 employees have overall favorable attitudes, with a composite mean score of 4.36 demonstrating moderate to high levels of engagement across key workplace indicators. The inconsistent recognition may have an impact on involvement, with the lowest mean of 3.80 and the biggest variability of 1.09. Meanwhile, semi-structured interviews were conducted with 12 administrative employees from a university in region 4A. The findings highlight factors influencing well-being, such as effective communication, work-life balance, positive office environments, and opportunities for promotion. Stress, heavy workloads, and insufficient recognition were seen to be significant challenges, whereas coping strategies including task prioritization, emotional regulation, and peer support were regarded as critical. The results show that well-being boosts commitment and productivity, whereas engagement improves mental health and job happiness. Universities must offer stress management, professional development, and recognition to improve results and staff engagement.